New Features of Cervical Cells for Cervical Cancer Diagnostic System Using Neural Network. - Mustafa, N; Mat Isa, N A; Mashor, M Y; Othman, N H (2007)

(untitled)
Currently, Pap test is the most popular and effective test for cervical cancer. However, Pap test does not always produce good diagnostic performance. This problem has encouraged several studies to develop diagnosis system based on neural networks to increase the diagnostic performance.